The applications of quantitative scanning transmission electron microscopy to the analysis of intracellular elemental distributions - Sheader, AA (2021)
The scanning transmission electron microscope (STEM) is an extraordinarily powerful tool for materials characterisation. The wealth of signals available in the microscope mean that chemical and structural details may be probed simultaneously, and often at the atomic scale. Recent developments in quantitative STEM methods have brought about new capabilities for acquiring mass and compositional information. In particular, advances in the measurement of the high-angle annular dark-field (HAADF) signal means it is now possible to count atoms within individual nanostructures with extremely high precision. In parallel, new approaches for quantifying energy-dispersive x-ray spectroscopy (EDX) and electron energy loss spectroscopy (EELS) data afford new opportunities for the determination of elemental composition on an absolute scale. Thus far, many of these emergent methods have seen little application outwith inorganic samples. This thesis aims to explore to what extent these advances can be applied in complex biological environments, with a particular focus on the measurement of intracellular elemental distributions. High-resolution imaging is first used to elucidate the nanoscale structure of two platinum-based chemotherapeutics. Similar methods are then used to identify single heavy atoms inside the cell bodies of dorsal root ganglia following Pt-drug administration. The use of quantitative HAADF STEM allows experimental measurements of atomic scattering cross- sections to be directly compared with those predicted from simulation. This ultimately confirms that the single atoms observed are indeed platinum, and allows the masses of small atomic clusters visualised in the cells to be measured. In later chapters, it is further shown that quantitative STEM imaging may be combined with spectroscopy to measure EDX and EELS partial scattering cross-sections. These are acquired for several elements of biological significance, including calcium, sodium and potassium. Finally, spectroscopic cross-sections are applied in samples of peripheral nerve to quantify aggregations of calcium in the mitochondria, and to measure changes in intra-axonal sodium and potassium levels following treatment with a chemotherapeutic agent.